FOLK SPEECH AND CULTURE OF THE REGION IN REPRESENTATION TO THE FOREIGN STUDENTS OF PHILOLOGICAL DEPARTMENT - Muratova, Maya (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
This article considers an actual problem of modern lingvomethodics which is the formation of lingvoregional knowledge and skills of foreign student-philologists. The main goal of this article is grounding and development of teaching materials which will form the lingvoregional knowledge and skills of the foreign students basing on the Pskov regional material.The article describes the following issues: students learn the peculiarities of local Pskov dialects, folk holidays of Pskov region, works of philologists and ethnographers devoted to the language and culture of Pskov. Main textual and lexicographical resources of the teaching materials are also covered, as well as the description of the introducing lingvoregional information methods. We also present the results of ascertaining and control experiment stages, during which the foreign students of the department of Russian Philology and Foreign languages were educated according to the introductory lingvoregional training program. During the experiment, we used the methods of linguistic-cultural analysis of words and text, the method of pedagogical experiment, mathematical method of processing the results obtained.The results of the tests showed that foreign students had significantly increased the level of linguistic and lingvoregional knowledge and skills, formed on the Pskov regional material.